Penanaman nasionalisme melalui pembelajaran budaya lokal di sekolah dasar Solafide Semarang - Welius Purbonuswanto; Mulyanto Darmowiyono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The research aims to instill Nationalist values through learning various local cultures of the local tribes in the Semarang Regency, West Nusa Tenggara. This research was conducted with a descriptive qualitative approach, and took the subject of primary school research at SD Solafide, Semarang Regency, by taking the school as a role model for inculcating the values of Nationalism through learning local culture. From the results of the study, it can be explained that the cultivation of nationalist values through learning local culture in elementary schools, especially Solafide Elementary School, is still not optimal and uneven. Most of the school teachers have not been conditioned to introduce the various cultures that are owned by the local tribes. This is evidenced that most elementary school students at SD Solafide are not familiar with the diverse local cultures. Elementary school students better understand and memorize dances of western, Indian, Korean and so on than local arts; then students are more familiar with various types of foreign food, more familiar with western culture than local local culture.